Holistic-Integrative Education System in an Islamic Kindergarten - Fauzi Fauzi (P3M STAIN Kudus, 2019)
This research aims at examining the holistic-integrative approach system model appliedto an Islamic Kindergarten in Purwokerto city, Banyumas Regency. This qualitative research employs acase study with observation, interview and documentation as the data collection techniques. The data are then analyzed using two analysis techniques, namely content analysis and comparative analysis, with an interactive cycle. Based on the findings, the education developed through thesystematic approach ranges from the input resourcesstrengthening process, processes and transformation of raw inputs involving process quality elements, setting output targets with clear and measurable characteristics, and orientation to education unit users. The Islamic Kindergarten’s system is formulated in an integrated holistic system format model of early childhood education (sources, environment, process, transformation, output, and user). The model is developed by the researcher out of Kaufman’s model and Smith’s modelfor general system approach model.